PASANG SURUT PERPOLITIKAN ISLAM DALAM KANCAH SEJARAH - Mansur (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2018)
This paper discusses the ups and downs of Islamic politics in the historical arena, the politics referred to in this paper is photographing the history of politics at the time of the Caliph or Companions and politics in the history of Islam. Political Islam is often seen as a combination of "religion and politics". The relationship between politics and religion is interrelated and inseparable, although technically and practically the relationship is distinguished, religion is the authority of Shahibu as-Shari'ah, while politics is public / human authority. But these two things go hand in hand just as the Islamic religion developed as a religious and political movement which in turn merged with the "public" state and society. The belief of a Muslim who considers that Islam is something that concerns the faith and politics and is rooted in the holy book of Islam "al-Qur'an" and the hadith of the Prophet, so that Muslims believe that this has been reflected in the teachings of Islam, its history, and political development.